Caffeine increases Nr1i3 expression and potentiates the effects of its ligand, TCPOBOP, in mice liver - Heidge Fukumasu; Arina Lázaro Rochetti; Andreia Oliveira Latorre; Pedro Ratto Lisboa Pires; Tereza Cristina Silva; Maria Lucia Zaidan Dagli (Universidade de São Paulo, 2015)
Caffeine is one of the world's most consumed substances. It is present in coffee, green tea and guarana, among others. The xenobiotic-sensing nuclear receptor subfamily 1, group I, member 3 (Nr1i3), also known as the Constitutive Androstane Receptor (Car) is a key regulator of drug metabolism and excretion. No consistent description of caffeine effects on this receptor has been described. Thus, to unravel the effects of caffeine on this receptor, we performed experiments in mice. First, C57Bl/6 mice that were treated daily with caffeine (50 mg/kg) for 15 days presented a slight but significant increase in Nr1i3 and Cyp2b10 gene expression. A second experiment was then performed to verify the effects of caffeine on TCPOBOP (1,4-bis-[2-(3,5-dichloropyridyloxy)]benzene, 3,3',5,5'-tetrachloro-1,4-bis(pyridyloxy)benzene), the most potent agonist known for mice Nr1i3. Interestingly, caffeine potentiated TCPOBOP pleiotropic effects in mice liver, such as hepatomegaly, hepatotoxicity, hepatocyte proliferation and loss of cell-to-cell communication through gap junctions. In addition, caffeine plus TCPOBOP treatment increased liver gene expression of Nr1i3 and Cyp2b10 comparing with only caffeine or TCPOBOP treatments. Together, these results indicate that caffeine increases the expression of Nr1i3 in mice liver, although at this point it is not possible to determine if Nr1i3 directly or indirectly mediates this effect.